S3EPY: a Sparky extension for determination of small scalar couplings from spin-state-selective excitation NMR experiments - Novák, Petr; Zídek, Lukás; Motácková, Veronika; Padrta, Petr; Svenková, Alzbeta; Nuzillard, Jean-Marc; Krásný, Libor; Sklenár, Vladimír (Journal of biomolecular NMR, 2010)
S3EPY is a Python extension to the program Sparky written to facilitate the assessment of coupling constants from in-phase/antiphase and spin-state-selective excitation (S(3)E) experiments. It enables the routine use of small scalar couplings by automating the coupling evaluation procedure. S3EPY provides an integrated graphical user interface to programs which outputs graphs and the table of determined couplings.
Keywords: Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; software; DNA-Directed RNA Polymerases; DNA řízené RNA-polymerasy; Software; User-Computer Interface; uživatelské rozhraní počítače; Bacillus subtilis